Le pèlerinage musical du chemin de Santiago de Compostelle / The Musical Pilgrimage of the Path of Santiago de Compostela - Luana Stan (Anastasis: Research in Medieval Culture and Art)
In the Middle Ages, in addition to Rome and Jerusalem, Santiago of Compostela was one of the three shrines to which every good Christian was to go to meditate and rejuvenate. But, unlike other famous locations, Santiago of Compostela was not known as a destination, but as a route: the way to become God’s pilgrim. The main source of the Jacobean cult is Liber Sancti Jacobi (The Book of Saint-Jacques), a twelfth century manuscript preserved in the Santiago cathedral, also known as Codex Calixtinus. Its first part is an anthology of liturgical pieces, while its fifth part is a true guide for pilgrimage. Marcel Pérès and his Ensemble Organum recreate the atmosphere of the Middle Ages music in a new, integrative, perspective which combines the Gregorian, the Byzantine and the Mozarabic chants. His Itinerant Center for the Research on the Ancient Music is situated in the Moissac Abbey, on the Compostela way.